2021
DOI: 10.1002/mp.15365
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric predictors and Lyman normal tissue complication probability model of hematological toxicity in cervical cancer patients with treated with pelvic irradiation

Abstract: Purpose To identify dosimetric parameters associated with acute hematological toxicity (HT) and identify the corresponding normal tissue complication probability (NTCP) model in cervical cancer patients receiving helical tomotherapy (Tomo) or fixed‐field intensity‐modulated radiation therapy (ff‐IMRT) in combination with chemotherapy, that is, concurrent chemoradiotherapy (CCRT) using the Lyman–Kutcher–Burman normal tissue complication probability (LKB‐NTCP) model. Methods Data were collected from 232 cervical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
(101 reference statements)
0
6
0
Order By: Relevance
“…The decrease in HGB in this study was associated not only with low-dose radiation but also with high-dose radiation. Wang [ 9 ] reached a similar conclusion that PBM dose irradiation of cervical cancer patients treated with CCRT and a process to both low-dose (V16-18) and high-dose (V35, 36 and V47) irradiation was associated with HT, depending on the fractional volumes receiving the variable degree of dosage.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The decrease in HGB in this study was associated not only with low-dose radiation but also with high-dose radiation. Wang [ 9 ] reached a similar conclusion that PBM dose irradiation of cervical cancer patients treated with CCRT and a process to both low-dose (V16-18) and high-dose (V35, 36 and V47) irradiation was associated with HT, depending on the fractional volumes receiving the variable degree of dosage.…”
Section: Discussionmentioning
confidence: 88%
“…Rose [ 5 ] and Albuquerque [ 6 ] reported that the volume of pelvic bone marrow (PBM) receiving low-dose radiation such as 10 Gy or 20 Gy is associated with HT among cervical cancer patients undergoing CCRT, while other studies [ 7 ] showed that the volume of BM receiving 40 Gy and the mean dose to BM correlated with higher rates of grade ≥ 2 HT. In addition, some studies [ 8 , 9 ] have suggested that acute HT in cervical cancer patients receiving CCRT is related to both low-dose and high-dose BM irradiation. Despite controversy, interest in dosimetric predictors of acute HT is still growing due to its clinical significance.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the incidence of grade ≥ 2 HT in uterine cervical cancer during chemoradiotherapy is 23-91.37% [ 5 , 8 , 21 ], and the incidence of grade ≥ 3 HT is 14.7-77% [ 10 , 14 , 21 , 22 ]. In this study, the incidence of grade ≥ 2 leukopenia, neutropenia, thrombocytopenia and anemia for patients with uterine cervical/endometrial cancer during radiotherapy was 63.9%, 45.4%, 19.6%, and 38.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Some low dose-volume parameters (such as V 10 and V 20 ) [ 4 8 ] and high dose-volume parameters (such as V 40 ) of the pelvic bone marrow have been related to acute HT [ 7 10 ]. Intensity-modulated radiation therapy (IMRT) can reduce the irradiated volume of the pelvic bone marrow [ 6 , 11 , 12 ] and reduce the risk of HT [ 4 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, personalized prediction models constructed by multiple predictors have been promoted and applied in several fields (13-15). Although many prediction models associated with cervical cancer have been developed, they are rarely used to predict the risk of acute HT (16,17). Many studies reported that the patient's status [age, body mass index (BMI)], tumor status, and treatment strategies (surgery, chemotherapy, radiotherapy) were possible risk factors causing HT, (8,9,16,18) but a comprehensive and convenient risk assessment system has not been established.…”
Section: Introductionmentioning
confidence: 99%